An Effectiveness Emla Used on School Aged Children’s Level of Pain During Venipuncture Procedure in Hospital - Tri Sakti Widyaningsih; Dwi Nur Aini (Humanistic Network for Science and Technology (HNST), 2019)
Pain that is not immediately cultivated can have a detrimental effect on children, including anxiety, sleep difficulties and despair. A child takes a series of procedures in a Hospital as a therapy. The first procedure often used on a child as he/she enters a hospital will be an intravenous therapy procedure and blood collection venipuncture. A topical anesthesia is often used in pediatric care. EMLA cream is an option to reduce pain during a venipuncture procedure on children. The research aims at know how the effectiveness of EMLA used on school aged child’s level of pain during venipuncture in Hospital. The research method of study used a quasi experimental post-test only non-equivalent control group. The sampling technique used consecutive sampling with a sample of 30 respondents consisted of two groups (intervention and control group). Bivariate analysis was carried out of using the Mann Withney test. The results indicated level of pain of children in the intervention group the majority experienced hurt little more 5.07%. The pain level in the majority control group experienced 8.53% is hurt worst. Based on the results of the study obtained a significant value was 0.000 (p